Progress in nucleic acid research and molecular biology. - Cohn, Waldo E.; Moldave, Kivie, 1923- (Progress in nucleic acid research and molecular biology, 1997)
"In perusing these chapters, I found much of interest. It is worth investigating."--Page Brickell in Biotechnology and Applied Biochemistry "Full of interest not only for the molecular biologist--for whom the numerous references will be invaluable--but will also appeal to a much wider circle of biologists, and in fact to all those who are concerned with the living cell."--British Medical Journal Key Features * Provides a forum for discussion of new discoveries, approaches, and ideas in molecular biology * Contributions from leaders in their fields * Abundant references